REGIONAL CHANGES IN SHORELINE. - Richards,Horace G. (1967)
Studies of Quaternary changes in shoreline have been carried out in different parts of the world. Part of this work was in cooperation with the Lamont Geological Observatory. Additional molluscan material was received from cores taken on the Argentina Shelf, the study of which confirms the previous evidence for a cold, shallow sea dating from Wisconsin time, work on the Canary Islands has yielded an extensive fauna. Absolute dating from one locality on Grand Canary suggests that the islands have been more stable than previously thought, the last major submergence having taken place during the Riss/Wurm interglacial. Similar conclusions were obtained from studies on some of the Bahama Islands. Miscellaneous studies were made on the Atlantic and Pacific Coasts of North America. Field work was done in Alaska and Japan in connection with a trip to the Pacific Science Congress in Tokyo. A study was made on some fossils in concretions dredged from Georges Bank. Miocene and Pleistocene species have been identified. (Author)